2021
DOI: 10.1177/23969415211045324
|View full text |Cite
|
Sign up to set email alerts
|

Teaching addition strategies to students with learning difficulties

Abstract: Background & aims In recent years, there has been an increased interest in analyzing the mathematical performance of students with learning difficulties in order to provide them with teaching methods adapted to their needs. In particular, the importance of studying the type of informal strategy that students use when solving problems has been highlighted. Observing how these strategies emerge and develop in children with learning difficulties is crucial, as it allows us to understand how they develop a sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Some studies have already shown that the strategies and representations used by ASD children are variables that determine their performance (Bruno et al, 2021 ; Polo Blanco et al, 2021 ; Polo-Blanco & González-López, 2021 ; Polo-Blanco et al, 2022 ). Others have shown that some of the cognitive traits intrinsic to the disorder, such as low executive functioning profile, can directly interfere with mathematical performance and with implementing the actions that are needed to solve mathematical problems (Bull & Scerif, 2001 ; Kim & Cameron, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have already shown that the strategies and representations used by ASD children are variables that determine their performance (Bruno et al, 2021 ; Polo Blanco et al, 2021 ; Polo-Blanco & González-López, 2021 ; Polo-Blanco et al, 2022 ). Others have shown that some of the cognitive traits intrinsic to the disorder, such as low executive functioning profile, can directly interfere with mathematical performance and with implementing the actions that are needed to solve mathematical problems (Bull & Scerif, 2001 ; Kim & Cameron, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they have direct implications on the design of educational interventions in ASD children with mathematical difficulties. For instance, as seen in other mathematical contexts, ASD children may not acquire advanced strategies spontaneously, as non-ASD children often do, so they may benefit from explicit instruction in strategy use (Polo-Blanco & González-López, 2021 ). Interventions should also consider stimulating the cognitive functions involved in mathematical problem solving that are most affected in ASD population (cognitive flexibility, inhibition, ToM and verbal comprehension) (Westby & Robinson, 2014 ; Whalon & Cox, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the inclusion of a checklist with guidelines for solving problems supports deficits in executive functions, such as planning, which are characteristic of individuals with ASD. In addition, as in other works that adapt methodologies for students with ASD (Polo-Blanco & García-Moya, 2021; Polo-Blanco et al, 2022; Root & Browder, 2019), modifications to the COMPS methodology have also been incorporated in this study. These include the pictogram sentences to support their understanding of the situation presented in the problem (García-Moya, 2018), the diagrams depicting the problem situation, as well as pictograms accompanying the instructions in the checklist.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a common approach, each participant required different reinforcements and adaptations of the instruction to develop the desired problem-solving skills. It is essential that teachers present a sufficient variety of problems, know these teaching methods, and make careful plans that are tailored to the specific needs of each student (Polo-Blanco & González, 2021; Polo-Blanco et al, 2019; 2021).…”
Section: Discussionmentioning
confidence: 99%